Reverse Remodeling in Human Heart Failure after Cardiac Resynchronization Therapy Is Associated With Reduced RHO-Kinase Activation - Ocaranza, Maria Paz; Jalil, Jorge E.; Altamirano, Rodrigo; León, Ana de; Moya, Jackeline; Lonis, Alejandra; Gabrielli, Luigi; Nab, Paul Mac; Córdova, Samuel; Paredes, Alejandro; Vergara, Ismael; Bittner, Alex; et al. (Frontiers in Pharmacology, 2021)
Background: Reverse remodeling is a clinically relevant endpoint in heart failure with reduced ejection fraction (HFrEF). Rho-kinase (ROCK) signaling cascade activation correlates with cardiac remodeling and left ventricular (LV) systolic dysfunction in HFrEF patients. Cardiac resynchronization therapy (CRT) is effective in HFrEF, especially when there is a left bundle block, as this treatment may stimulate reverse remodeling, thereby improving quality of life and prolonging survival for patients with this severe condition. Here, we evaluate the hypothesis that ROCK activation is reduced after effective CRT in HFrEF. Methods: ROCK activation in circulating leukocytes was evaluated in 28 HFrHF patients, using Western blot (myosin light chain phosphatase subunit 1 phosphorylation, MYPT1p/t), before and three months after initiation of CRT. LV systolic function and remodeling were assessed by echocardiography. Results: Three months after CRT, LV ejection fraction increased an average of 14.5% (p < 0.001) in 13 patients (responders), while no change was observed in 15 patients (non-responders). End-systolic diameter decreased 16% (p < 0.001) in responders, with no change in non-responders. ROCK activation in PBMCs decreased 66% in responders (p < 0.05) but increased 10% in non-responders (NS). LV end-diastolic diameter was also 5.2 mm larger in non-responders vs. responders (p = 0.058). LV ejection fraction, systolic diameter, and ROCK activation levels were similar in both groups at baseline. Conclusion: In HFrEF patients, 3 months of effective CRT induced reverse myocardial remodeling, and ROCK activation was significantly decreased in circulating leukocytes. Thus, decreased ROCK activation in circulating leukocytes may reflect reverse cardiac remodeling in patients with heart failure.